A Systematic Review ofthe Maternal and Child Health System in India - CharulChhokra (International Journal of Psychosocial Rehabilitation, 2020)
The study investigates “the prevalence and causes related to the use of maternal and child health services by married young women in India.” Results “indicate that the use of maternal and newborn health facilities by teenage women in India is far from adequate. A little over 10% of young women used antenatal treatment, about 50% used healthy contraceptive services, and about 41% of children received complete immunization.” Major disparities have arisen in urban-rural residency due to some factors such as “educational qualifications, gender roles, economic conditions, etc., which are also the main determinants of the use of maternal and child health services.” Health care services should focus primarily on teaching young women, offering financial assistance, increasing awareness, and giving guidance to married adolescent couples. In addition, sufficient financial support for the birth and care of married women under the age of 19 should be given to strengthen the maternal and newborn health system in India.